Peer Score Presentation in Non-English Department Classes: Investigating Students’ Perceptions to Boost Confidence - Rizky Amelia (Universitas Maritim Raja Ali Haji (UMRAH), 2024)
English is a required course during the first and second semesters learning in Vocational Higher Education in Indonesia. Recognizing the importance of future career demands, presentation skills are incorporated into the Semester Learning Plans as English for Specific Purposes. This research focuses on students' perspectives regarding English learning through presentations regarding their own field particularly the implementation of peer scoring. Employing a qualitative descriptive approach, the study involved first-semester students at Politeknik Negeri Banjarmasin. One hundred and fifteen students of Banjarmasin State Polytechnic, Indonesia majoring in Mining Engineering (19 students), Civil Engineering (35 students) and Accounting (61 students) responded to a questionnaire, and ten students were interviewed, serving as voluntarily participants. Data collection method included a questionnaire administered via Google Form and interviews for triangulation. Students filled in the questionnaire after scoring their peer’s presentation. In scoring their peers, they used a presentation scoring rubric. Findings indicate a generally positive perception among students towards peer scoring presentations. Despite experiencing anxiety during preparation and delivery of presentation, students expressed high motivation and found the presentation experience rewarding as the scores not only from the lecturer but also from their peers. They worried to score at the beginning, but the scoring rubric help them guide along the process. Some students who commonly do not pay attention to the presenters in the presentation are now fully paying attention because they are in charge to score. Overall, students viewed presentation projects favorably, highlighting their potential to improve speaking performance and be a rater on their peers’ performance. The implication of this research is to highlight students’ ability to deliver a presentation as well as build their confidence in speaking activities.